Analisis Retorika Aristoteles (Ethos, Pathos, dan Logos) Dalam Video Khutbah Idul Adha Ustad Abdul Somad “Harta Hanyalah Titipan, Sudahkah Kamu Berqurban?” - Sundari Sundari; Rhani Febria (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to describe the use of Aristotle's rhetoric including ethos, pathos, and logos in the video of Ustaz Abdul Somad's Eid al-Adha sermon entitled "Wealth is Only a Deposit, Have You Sacrificed?". This study uses a qualitative approach with a content analysis method. The research data source is a sermon video uploaded through the Ustaz Abdul Somad Official YouTube channel. The research data is in the form of speech containing elements of ethos, pathos, and logos, which are collected through listening and note-taking techniques. Data analysis is carried out through the stages of identification, classification, interpretation, and presentation of data based on Aristotle's rhetorical theory. The results show that there are 15 data consisting of 4 ethos data, 6 pathos data, and 5 logos data. The ethos element is shown through the use of verses from the Qur'an, hadith, opinions of scholars, and stories of Islamic figures that serve to strengthen the speaker's credibility. The pathos element is seen through speech that is able to arouse the audience's emotions, such as emotion, gratitude, empathy, admiration, and compassion. Meanwhile, the element of logos is manifested through logical argumentation, causal relationships, solutions, and rational explanations of religious concepts. Research findings indicate that these three rhetorical elements are used in an integrated manner, increasing the effectiveness of the delivery of the da'wah message and strengthening the persuasive power of Ustaz Abdul Somad's sermon.